Cytokine Secretion in Macrophages: SNAREs, Rabs, and Membrane Trafficking - Murray, Rachael Zoe; Stow, Jennifer Lea (Frontiers in Immunology, 2014)
Macrophages have the capacity to rapidly secrete a wide range of inflammatory mediators that influence the development and extent of an inflammatory response. Newly synthesized and/or preformed stored cytokines and other inflammatory mediators are released upon stimulation, the timing and volume of which is highly regulated. To finely tune this process secretion is regulated at many levels; at the level of transcription and translation and posttranslationally at the ER, Golgi and at or near the cell surface. Here we discuss recent advances in deciphering these cytokine pathways in macrophages, focusing on recent discoveries regarding the cellular machinery and mechanisms implicated in the synthesis, trafficking and secretion of cytokines. The specific roles of trafficking machinery including chaperones, GTPases, cytoskeletal proteins and SNARE membrane fusion proteins will be discussed.